THE ROLE OF THE ENGLISH LANGUAGE IN THE TEACHING OF INVERTEBRATE ZOOLOGY IN HIGHER EDUCATIONAL INSTITUTIONS (World Bulletin of Social Sciences, 2024)
In the article, in teaching the science of invertebrate zoology in higher educational institutions, the students are to develop skills using elements of the English language, to justify the skills of independent thinking and their practical application, and the object taken as an example is the morphophysiology of the family of ants (Formicidae) and the main differences from other representatives of insects, as well as vocabulary from the English language for mastering the subject.